Pengenalan Komputer Dasar Di SMP Muhammadiyah -35 Sigambal - Purba, Elvitrianim (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2024)
Mastery of information and communication technology is a fundamental need in today's world of education. This community service aims to provide an introduction to basic computers to students at SMP Muhammadiyah -35 Sigambal. This activity is designed to improve students' digital literacy through the introduction of computer hardware and software components, as well as the basics of using word processing applications and the internet. The implementation method includes counseling, direct demonstrations, and practical exercises. The results of this activity show that students have an increased understanding and basic skills in using computers. It is hoped that this activity can be the first step for students to be more skilled in utilizing technology in the learning process.